2007
DOI: 10.1038/sj.npp.1301493
|View full text |Cite
|
Sign up to set email alerts
|

Issues that May Determine the Outcome of Antipsychotic Trials: Industry Sponsorship and Extrapyramidal Side Effect

Abstract: This study presents a meta-analysis of the influence of several potentially biasing factors (eg industry support, extrapyramidal side effects) on efficacy of studies comparing second-generation antipsychotic (SGA) with first-generation antipsychotic (FGA) medications. We used the dataset from our previously published meta-analysis of 124 randomized controlled trials (RCTs) comparing SGAs with FGAs, to evaluate whether certain possible biases could influence the actual outcome on the total score of the Positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The ORs in for-profit-funded research in these studies have not been statistically different from nonprofit-funded studies [5, 17, 18]. Two exceptions are trials investigating nicotine replacement therapy [19] and glucosamine [20].…”
Section: Discussionmentioning
confidence: 97%
“…The ORs in for-profit-funded research in these studies have not been statistically different from nonprofit-funded studies [5, 17, 18]. Two exceptions are trials investigating nicotine replacement therapy [19] and glucosamine [20].…”
Section: Discussionmentioning
confidence: 97%
“…"Effectiveness" trials, not supported by industry, are proposed as better reflecting the results to be expected in clinical practice (66). Drug company sponsorhip has now been shown not to lead to bias in randomized controlled trials of APDs (67). The CATIE trial, sponsored by the National Institute of Mental Health, enrolled 1,493 patients and was to be the largest and longest (up to 18 months) doubleblind randomized effectiveness trial comparing a typical APD (perphenazine) and four atypical APDs (olanzapine, quetiapine, risperidone, and ziprasidone).…”
Section: Use Of Atypical Apds In Non-treatment-resistant Schizophreniamentioning
confidence: 99%
“…Data are mixed on the relationship between research report quality and the funding source across healthcare disciplines [6], [19][22]. Findings indicate that the relationship may vary by the segment of industry or subspecialty (e.g., knee construction, spine, trauma), the type of support (e.g., stock ownership, speaking engagements, or grant receipt), and the type of trial (e.g., drug trial, surgical trial, or other therapies) [7], [10], [11], [23]. Similar data on nutrition-related topics are limited, and some studies have indicated that industry-funded research reports may be of equal or higher quality than non-industry-funded nutrition-related research [24][26].…”
Section: Introductionmentioning
confidence: 98%
“…As diagrammed in Figure 1, and reported by several authors, there is potential for bias to enter during the phase of primary research and when published studies are reviewed and synthesized for evidence analysis or review papers [2][6]. Studies investigating both non-nutrition-related and nutrition-related research have reported that published findings are likely to favor funder interests [7][14]. If this phenomenon were due to researchers with a vested interest in the outcomes of the research being less rigorous in their adherence to standards of execution or reporting of scientific research and thus, consciously or unconsciously skewing their findings in favor of the preferred outcome, it would likely be reflected in lower research report quality ratings when research reports are reviewed and appraised for inclusion in systematic reviews.…”
Section: Introductionmentioning
confidence: 99%